(untitled) (Journal of Informatics and Mathematical Sciences, 2021)
The study of Arterial blood flow is a fascinating topic as arterial disease is responsible of death in many nations. This paper investigated the conduct of blood flow across a tapered artery with stenosis. This study has been simply explained by the use of a mathematical model that is appropriate. The graphical representations were created to support the results of the study. For various values of tapering angle, it is discovered that wall shear stress enhance when a peak is reached, then decreases. We also found that the velocity of the blood flow reduces with radius and also for distinct values of tapering angle. It is also evidenced that the blood flow rate reduces as the radius and tapering angle increase.